Unraveling the Pathway from Digital Leadership to Employee Creativity: The Strategic Roles of Intrinsic Motivation and Job Engagement - Maria Valeria Roellyanti; Muafi Muafi; Dessy Isfianadewi (Environment and Social Psychology, 2026)
This study develops a theoretical model explaining how digital leadership fosters employee creativity through the psychological mechanisms of intrinsic motivation and job engagement, addressing inconsistent prior findings and the limited evidence from Indonesia’s private banking sector. Using a quantitative survey of 250 private bank employees in the Special Region of Yogyakarta, data were analyzed with PLS-SEM to evaluate both the measurement and structural models, including reliability, validity, predictive power, and path relationships. The results confirm all hypothesized direct and indirect effects, indicating that digital leadership positively influences intrinsic motivation and job engagement, which in turn enhance employee creativity. Both variables function as significant mediators, and the model demonstrates moderate predictive relevance without multicollinearity issues. The study contributes to organizational and human resource management literature by extending digital leadership research in highly regulated, technology-intensive contexts and reinforcing the explanatory role of Self-Determination Theory in the digital era. Practically, the findings emphasize the importance of developing digital leadership capabilities, promoting autonomy and continuous skill development, and leveraging job engagement as a strategic driver of sustainable creativity in Indonesia’s banking sector.